A Simplified System to Express Circularized Inhibitors of miRNA for Stable and Potent Suppression of miRNA Functions - Yi Shu; Ke Wu; Zongyue Zeng; Shifeng Huang; Xiaojuan Ji; Chengfu Yuan; Linghuan Zhang; Wei Liu; Bo Huang; Yixiao Feng; Bo Zhang; Zhengyu Dai; et al. (Elsevier, 2018)
MicroRNAs (miRNAs) are an evolutionarily conserved class of small regulatory noncoding RNAs, binding to complementary target mRNAs and resulting in mRNA translational inhibition or degradation, and they play an important role in regulating many aspects of physiologic and pathologic processes in mammalian cells. Thus, efficient manipulations of miRNA functions may be exploited as promising therapeutics for human diseases. Two commonly used strategies to inhibit miRNA functions include direct transfection of chemically synthesized miRNA inhibitors and delivery of a gene vector that instructs intracellular transcription of miRNA inhibitors. While most miRNA inhibitors are based on antisense molecules to bind and sequester miRNAs from their natural targets, it is challenging to achieve effective and stable miRNA inhibition. Here we develop a user-friendly system to express circular inhibitors of miRNA (CimiRs) by exploiting the noncanonical head-to-tail backsplicing mechanism for generating endogenous circular RNA sponges. In our proof-of-principle experiments, we demonstrate that the circular forms of the hsa-miR223-binding site of human β-arrestin1 (ARRB1) 3' UTR sponge RNA (BUTR), the bulged anti-miR223 (cirBulg223) and bulged anti-miR21 (cirBulg21), exhibit more potent suppression of miRNA functions than their linear counterparts. Therefore, the engineered CimiR expression system should be a valuable tool to target miRNAs for basic and translational research. Keywords: microRNA, miRNA, miRNA sponge, circular RNA, miRNA inhibitor, competing endogenous RNA, miRNA decoy, noncoding RNA, oncomiR